Data Mining Techniques for Estimation of Wind Speed Using Weka - Hari Mallikarguna Reddy, B; Venkatramana Reddy, S; Sarojamma, B (International Journal of Computer Sciences and Engineering, 2021)
Now a day’s neural network plays a vital role in analyzing, interpreting and fitting models. In this paper by taking wind speed as dependent variable and minimum temperature, maximum temperature, visibility, temperature date and time as independent variables, we fitted. M5P, SMO Regression and zero regression models and CV parameter selection criteria is also used for above three models. For computational purpose WEKA Software is used. By measures of accuracy like mean absolute error, root mean square. Relative absolute error, root relative squared error are used to select the best model and also rank them.